Is the Focus on “Ecosystems” a Liability in the Research on Nature's Services? - Baveye, Philippe C.; Chalhoub, Maha; Choquet, Pauline; Montagne, David (Frontiers in Ecology and Evolution, 2018)
For the last 20 years, the concept of ecosystem has constituted one of the key pillars on which the study of “ecosystem services”, i.e., the benefits that human populations derive from nature, has been based. Yet, at this stage, one could argue that, in general and especially in fields related to agriculture, the ecosystem framework tends to limit unnecessarily the range of benefits to humans that are considered in practice, to hinder the necessary measurement of services, and to make it challenging to convince individuals to take nature’s services into account in their decision making. In the present Perspective piece, we analyze these 3 arguments in detail, conclude that the current focus on ecosystems is more a liability than an asset in the field, and suggest a return to the less constraining notions of “nature’s functions and services”, without a necessary tie to ecosystems.